Kajian Sosiologi Kriminal : Desakan Masyarakat Muslim Kebumen Pelarangan Minuman Keras - Isima, Nurlaila; Isima, Astri (Program Studi Sosiologi Agama Fakultas Ushuluddin, Adab dan Dakwah IAIN Manado, 2023)
This study aims to analyze the position of the Muslim community in the study of criminal sociology in participating in prohibiting alcohol consumption in Kebumen Regency. This research is qualitative research with a sociological approach to crime. This research shows that the views of the Muslim community in Kebumen are in line with the views on the prohibition of khamar following Islamic religious law. Supported by the negative impact of alcohol consumption felt by the community, encouraging public awareness to urge local governments to ratify Perda No. 3 Tahun 2010 tentang Pengendalian dan Pengawasan Minuman Keras. However, if examined from criminal policy, the existence of Regional Regulations only related to oil control, not as expected in the prohibition of alcohol consumption.